Medium to long-term results of 130 Ankle Evolutive System total ankle replacements—Inferior survival due to peri-implant osteolysis. Issue 2 (June 2017) - Koivu, Helka; Kohonen, Ia; Mattila, Kimmo; Loyttyniemi, Eliisa; Tiusanen, Hannu
Highlights: High amount of peri-implant osteolysis with AES total ankle replacement. The outcome and survival of AES TAR is impaired by peri-implant osteolysis. Postoperative varus malalignment is associated with poor implant survival in TAR. Abstract: Background: The study reports the medium to long-term results of 130 Ankle Evolutive System total ankle replacements operated at a single-centre. Previously high amount of peri-implant osteolysis was reported from the same material. Methods: Between 2002 and 2008 one hundred and thirty consecutive ankles replaced with AES ankle prosthesis were followed both radiologically and clinically. Results: The five-year survival was 87.3% (95% confidence interval (CI) 80.0–92.0%), and ten-year survival 74.9% (95% confidence interval (CI) 65.4–82.2%) at a median follow-up time of 96 months (range 2–161; 8 years). Peri-implant osteolysis was found in 91 (70%) ankles, marked in 78 (60%). 44 ankles (34%) have been revised by filling of the cavities, 24 (18%) by fusion, and 6 by further replacement, resulting in the revision rate of 58%. Osteolysis was the main reason for all revisions. The improvement of the Kofoed Score and pain points was significant (all p < 0.0001), and the subjective patient satisfaction was good. Conclusions: Outcome of the current study was seriously affected by osteolysis and is inferior compared to previous reports.